Teaching writing and reading skills. An experience with Chinese “letters”. - Querol Bataller, María (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
Different constructivist proposals on learning writing and reading skills have not only allowed us to show the different stages and hypotheses that children establish around written language but also to elaborate, in accordance with those parameters, some methodological and didactic proposals for their teaching and learning. Along the following pages, we present a proposal aiming at, firstly, leading the Education students to re-live the process of learning the written language (together with the implications involved in lacking in that skill). The second aim is for the students to experience it through a methodology that is typically analytical or global (a methodology with which most of the students in the course are not familiar). In order to do that, several practical experiences with Chinese language are explained. These will allow future teachers to re-live the written language learning process, and also how could be living without that knowledge. Lastly, they will try to learn writing-learning skills with analytic or whole-word methods.